2016
DOI: 10.16949/turkbilmat.267339
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personalisation of Instruction on Students’ Motivation to learn Mathematics Word Problems in Nigeria

Abstract: This study investigated the effect of personalisation of instruction on the motivation to learn mathematics word problems of 450 senior secondary students in Nigeria within the blueprint of quasiexperimental research of Solomon Four non-equivalent control group design. It also examined the influence of gender on motivation to learn mathematics word problems and personalisation was accomplished by incorporating selected information with students" personal preferences into their mathematics word problems. Motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
6
15
1
1
Order By: Relevance
“…The non-significant main effect of gender on students' achievement in mathematics in this study (Table 3) was in agreement with the results of previous studies in mathematics (Awofala, 2017;Fatade, Nneji, Awofala & Awofala, 2012;Awofala & Anyikwa, 2014;Awofala, 2016). These studies reported that there are no significant gender differences in students' learning outcomes.…”
Section: Resultssupporting
confidence: 92%
“…The non-significant main effect of gender on students' achievement in mathematics in this study (Table 3) was in agreement with the results of previous studies in mathematics (Awofala, 2017;Fatade, Nneji, Awofala & Awofala, 2012;Awofala & Anyikwa, 2014;Awofala, 2016). These studies reported that there are no significant gender differences in students' learning outcomes.…”
Section: Resultssupporting
confidence: 92%
“…The results indicated that students' achievement in algebra was greatly improved when they were exposed to the teaching strategies of blended learning and problem-based learning when compared with the traditional lecture method. This finding supported earlier findings (Awofala, 2017b;Awofala, etal., 2013;Akay & Boz, 2010;Akinsola & Awofala, 2009Awofala, Fatade & Olaoluwa, 2013Awofala, Balogun & Olagunju, 2011;Nicolaou & Philippou, 2004;Akinsola & Tella, 2003;Awofala, 2011) which associated improved content learning to learner-centred teaching strategies.…”
Section: Main Effect Of Treatment (Pbl Bl and Traditional Lecture Msupporting
confidence: 94%
“…e result agrees with the findings of Bassey et al [48] that students with analytic cognitive style had higher significant mean achievement score than those with relational and inferential cognitive style. However, the result disagrees with the findings of Awofala et al [49] that students with nonanalytic cognitive style had higher mean achievement score than students with analytic cognitive style. On similar studies in English language [6,14] reported that global learners performed significantly better than their analytic counterparts in ESL/EFL classroom.…”
Section: Discussion Of the Resultcontrasting
confidence: 99%